Preparation process of Fe3C / biomass carbon composite material with S-band wave absorbing performance
Through the preparation process of Fe3C/biomass carbon composite materials, the existing absorbent materials have high density, high cost and narrow absorption frequency bands have been solved, and efficient S-band electromagnetic wave absorption is achieved, which is suitable for large-scale production and has good chemical stability.
Patent Information
- Application Number
- CN202411713683.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electromagnetic wave absorbing materials have problems such as high density, high production costs, and narrow absorption frequency bands. In particular, there is a lack of efficient low-frequency band absorbing materials, which is difficult to meet the increasingly serious electromagnetic pollution problem.
The preparation process of Fe3C/biomass carbon composite material is adopted to obtain an absorbent material with S-band absorbing properties by modifying sugarcane fibers under a high temperature alkaline environment and impregnating with iron salt solution at room temperature, and then sintering under a protective atmosphere.
It realizes efficient low-frequency (S-band) electromagnetic wave absorption capacity, has the characteristics of low preparation cost, thin matching thickness, and multiple loss mechanisms, is suitable for large-scale production, and has good chemical stability of the materials.
Smart Images

Figure CN119503805A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electromagnetic functional materials, and in particular relates to a preparation process of a Fe3C / biomass carbon composite material with S-band wave absorbing performance. Background Art
[0002] In recent years, with the continuous development of electronic communication technology, the harm of electromagnetic pollution generated by various electronic products to the environment and human body has attracted more and more attention. However, the use of traditional absorbing materials is limited by their high density, high production cost, narrow absorption band, etc., especially the lack of efficient absorbing materials in lower frequency bands. Therefore, the industry is in urgent need of an economical and efficient absorbing material to solve the increasingly serious electromagnetic pollution problem.
[0003] The electromagnetic pollution that people are currently facing has the characteristics of wide frequency band and wide distribution, which requires the absorbing materials to have broadband and efficient absorbing capabilities, while also reducing costs. In response to this problem, absorbing materials with a single component and structure are often difficult to meet the performance requirements of high efficiency and broadband, so it is necessary to introduce multiple electromagnetic loss mechanisms. For example, the patent with application number CN202211308642.9 discloses a low calcination temperature MOF-derived carbon-based absorbing material. By controlling the composition of metal nanoparticles wrapped in the carbon layer, the low calcination temperature is used to prepare high-performance MOF-derived carbon-based absorbing materials, which can increase the reflection path of electromagnetic waves and promote multiple losses of electromagnetic waves in the material. However, its preparation process is complicated and the cost is high, which is not conducive to large-scale production. The patent with application number CN113023723B discloses a biochar absorbing material based on grapefruit peel, which recycles agricultural production waste, but the electromagnetic wave absorption performance of this product still has room for improvement and is difficult to meet current use. The patent with application number CN202110510933.5 discloses a method for preparing biomass porous carbon absorbing material. It utilizes the special structure of laver to carbonize at high temperature and retains its porous structure. However, there is a problem of single electromagnetic wave loss mode, especially the absorption effect in low frequency bands (L and S bands) is poor. If multiple loss modes are introduced, there may be better electromagnetic wave absorption effect.
[0004] Therefore, the pursuit of high efficiency, light weight and low cost is the current focus of research and development of new electromagnetic wave absorbing materials. Among them, carbon-based materials have low density and high conductivity, and the composite and structural construction of different materials will have different properties, which has great research and application value and is worth exploring. Summary of the invention
[0005] The present invention aims to solve the problems existing in the prior art and provides a preparation process of Fe3C / biomass carbon composite material with S-band absorbing performance. The absorbing material designed by the present invention has the characteristics of high absorption performance, excellent low-frequency absorption capacity, thin matching thickness, low preparation cost, etc.
[0006] The preparation process of the Fe3C / biomass carbon composite material with S-band absorbing performance of the present invention comprises the following steps: firstly, modifying sugarcane fiber in a high-temperature alkaline environment; then impregnating the obtained plant fiber and an iron salt solution at room temperature to obtain a mixture; and finally, sintering in a protective atmosphere to realize two processes of carbonization and in-situ growth to obtain the Fe3C / biomass carbon composite absorbing material.
[0007] The specific steps include: Step 1: Add sugarcane fiber to NaOH solution, stir and modify it at 100°C for 3-4 hours, filter, repeatedly wash the sugarcane fiber with deionized water until the pH of the filtrate is neutral, and obtain modified sugarcane fiber after drying.
[0008] Step 2: Add the modified sugarcane fiber obtained in step 1 to the ferric nitrate nonahydrate solution, stir at room temperature for 12 hours, and then completely dry the solid-liquid mixture at 70° C. to obtain a precursor.
[0009] Step 3: Sinter the precursor obtained in step 2 in a nitrogen atmosphere to obtain a fibrous Fe3C / biomass carbon composite absorbing material.
[0010] Step 4: Put the fiber material obtained in step 3 into a mortar and grind it to obtain a powdered Fe3C / biomass carbon composite absorbing material.
[0011] In step 1, the mass concentration of the NaOH solution is 1%.
[0012] Furthermore, the volume of the NaOH solution was 100 mL, and the amount of sugarcane fiber added was 4 g.
[0013] In step 2, the concentration of the ferric nitrate nonahydrate solution is 0.03-0.07 mol / L.
[0014] Furthermore, the volume of the ferric nitrate nonahydrate solution was 50 mL, and the amount of modified sugarcane fiber added was 1.5 g.
[0015] In step 3, the sintering temperature is 750° C. and the holding time is 3 h.
[0016] In step 4, the grinding time is 20 min.
[0017] The absorbing powder material of the present invention is mainly composed of carbon material and nanometer-level Fe3C particles are grown in situ on the flaky carbon structure. The plant fiber structure is made fluffy and some organic impurities are removed by high-temperature treatment in an alkaline environment. The modified plant fiber is then mixed with a ferric nitrate solution and evaporated to dryness, and carbonized at high temperature in a nitrogen atmosphere while growing in situ to obtain a lightweight electromagnetic wave absorbing material with a flaky carbon structure.
[0018] The beneficial effects of the present invention are embodied in: 1. The present invention utilizes the flake structure of bagasse fiber to form a high dielectric carbon structure material after carbonization at high temperature, and the surface of the flake carbon material is modified by Fe3C nanoparticles with high reflection and high magnetic loss. After grinding, the flake particles modified by Fe3C nanoparticles are stacked on each other to form a three-dimensional structure. Based on its special structure, it has multiple loss mechanisms, which greatly improves the absorption effect.
[0019] 2. Compared with similar products on the market, the present invention has better electromagnetic wave absorption capacity and exhibits excellent electromagnetic wave absorption capacity in a lower frequency band (S band).
[0020] 3. The present invention uses sugarcane fiber as raw material, which not only utilizes the thin sheet structure of sugarcane fiber, but also takes into account production costs and environmental protection issues, and achieves the recycling of agricultural waste, making the production of high-efficiency electromagnetic absorption materials more green and economical. Its low production cost facilitates large-scale production.
[0021] 4. The one-step heat treatment in-situ growth process used in the present invention can control the distribution density of Fe3C nanoparticles on the surface of the thin carbon structure by controlling the concentration of iron ions, thereby realizing the preparation of adjustable electromagnetic wave absorbing materials.
[0022] 5. The material prepared by the present invention is a composite material composed of C and Fe3C. Both materials have good chemical stability, so the composite material can meet the stability requirements in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the SEM image of the composite material of Example 1. Figure 1(a) and (b) are microscopic characterization pictures of the composite material after high-temperature sintering without grinding. It can be seen that the Fe3C particles are evenly and densely distributed on the surface of the planar plant fiber. Figure (c) shows the spatial structure formed by the stacking of thin flake particles after the sample is ground. Figure (d) shows that the Fe3C particles are also evenly and densely distributed on the surface of each thin flake particle.
[0025] Figure 2 This is the XRD pattern of the sample in Example 1.
[0026] Figure 3 This is the reflection loss (RL) curve of the sample in Example 1 at 2~18GHz.
[0027] Figure 4 This is the reflection loss (RL) curve of the sample in Example 2 at 2~18GHz.
[0028] Figure 5 This is the reflection loss (RL) curve of the sample in Example 3 at 2~18GHz.
[0029] Figure 6 This is the reflection loss (RL) curve of the sample in Example 4 at 2~18GHz.
[0030] Figure 7 The figure is the process route diagram of the present invention. DETAILED DESCRIPTION
[0031] The embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. Obviously, what is shown in the present invention are only some embodiments of the present invention, not all embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Embodiment 1:
[0032] The preparation method of the Fe3C / biocarbon composite absorbing material in this embodiment includes the following steps: 1. Prepare 100 mL of NaOH solution A with an alkali concentration of 1%, weigh 4 g of sugarcane fiber and solution A, stir at 100 ° C for 4 hours, and then filter out the sugarcane fiber with a filter; repeatedly wash the sugarcane fiber with deionized water until the pH of the filtered liquid is neutral, and then evaporate the sugarcane fiber in an oven to obtain modified sugarcane fiber.
[0033] 2. Prepare 50 mL of ferric nitrate nonahydrate solution B with a molar concentration of 0.03 mol / L, weigh 1.5 g of modified sugarcane fiber and mix with solution B, stir at room temperature for 12 h to obtain a solid-liquid blend; completely dry the solid-liquid blend at 70° C. to obtain a precursor.
[0034] 3. The obtained precursor was evenly spread on the bottom of the crucible, and kept at 750°C for 3 hours under nitrogen protection to obtain a fibrous composite material.
[0035] 4. Put the obtained fiber composite material into a mortar and grind it for 20 minutes to obtain a powdered Fe3C / biomass carbon composite absorbing material.
[0036] The absorbing performance of the Fe3C / biochar composite absorbing material prepared in this embodiment was tested using a vector network analyzer. During the test, the absorbing material powder of the present invention and solid paraffin were uniformly mixed in a mass ratio of 3:7 and made into a ring-shaped sample, and its reflection loss (RL) was tested in the 2-18 GHz electromagnetic wave frequency band. Figure 1 Figure 3 is the SEM image of Fe3C / biochar composite material. (a) and (b) are microscopic characterization pictures of the composite material after high-temperature sintering without grinding. It can be seen that the Fe3C particles are evenly and densely distributed on the surface of the planar plant fiber. Figure (c) is the spatial structure formed by the stacking of thin flake particles after the sample is ground. Figure (d) shows that the Fe3C particles are also evenly and densely distributed on the surface of each thin flake particle. Figure 2 The XRD image of the Fe3C / biocarbon composite material prepared in this embodiment shows that the curve is at 37.6 。 , 44.6 。 , 45.8 。 , 54.4 。 , 57.9 。 There are five obvious diffraction peaks, which correspond to the (121), (220), (112), (230), and (301) planes of Fe3C respectively. Figure 3 This is the RL curve of the sample in this embodiment at 2-18 GHz. It can be seen that the composite material has an RL value of up to -64.98 dB at 5.6 GHz in the C band when the thickness is 3.6 mm, and the material has an RL value of up to -57.48 dB at 4.24 GHz in the C band when the matching thickness is 4.5 mm. Embodiment 2:
[0037] The preparation method of the Fe3C / biocarbon composite absorbing material in this embodiment includes the following steps: 1. Prepare 100 mL of NaOH solution A with an alkali concentration of 1%, weigh 4 g of sugarcane fiber and solution A, stir at 100 ° C for 4 hours, and then filter out the sugarcane fiber with a filter; repeatedly wash the sugarcane fiber with deionized water until the pH of the filtered liquid is neutral, and then evaporate the sugarcane fiber in an oven to obtain modified sugarcane fiber.
[0038] 2. Prepare 50 mL of ferric nitrate nonahydrate solution B with a molar concentration of 0.05 mol / L, weigh 1.5 g of modified sugarcane fiber and mix it with solution B, stir at room temperature for 12 hours to obtain a solid-liquid blend; completely dry the solid-liquid blend at 70°C to obtain a precursor.
[0039] 3. The obtained precursor was evenly spread on the bottom of the crucible, and kept at 750°C for 3 hours under nitrogen protection to obtain a fibrous composite material.
[0040] 4. Put the obtained fiber composite material into a mortar and grind it for 20 minutes to obtain a powdered Fe3C / biomass carbon composite absorbing material.
[0041] The absorbing performance of the Fe3C / biochar composite absorbing material prepared in this embodiment was tested using a vector network analyzer. During the test, the absorbing material powder of the present invention and solid paraffin were uniformly mixed in a mass ratio of 3:7 and made into a ring-shaped sample, and its reflection loss (RL) was tested in the 2-18 GHz electromagnetic wave frequency band. Figure 4 This is the RL curve of the sample in this embodiment at 2~18GHz. It can be seen that when the composite material is 4.9mm thick, the material achieves dual-frequency absorption in the C and Ku bands, and obtains an RL value of up to -25.34dB at 4.68GHz in the C band. When the matching thickness is 5.4mm, the material achieves dual-frequency absorption in the S and X bands, and the RL at 2.96GHz in the S band reaches -61.29dB. Embodiment 3:
[0042] The preparation method of the Fe3C / biocarbon composite absorbing material in this embodiment includes the following steps: 1. Prepare 100 mL of NaOH solution A with an alkali concentration of 1%, weigh 4 g of sugarcane fiber and solution A, stir at 100 ° C for 4 hours, and then filter out the sugarcane fiber with a filter; repeatedly wash the sugarcane fiber with deionized water until the pH of the filtered liquid is neutral, and then evaporate the sugarcane fiber in an oven to obtain modified sugarcane fiber.
[0043] 2. Prepare 50 mL of ferric nitrate nonahydrate solution B with a molar concentration of 0.07 mol / L, weigh 1.5 g of modified sugarcane fiber and mix it with solution B, stir at room temperature for 12 hours to obtain a solid-liquid blend; completely dry the solid-liquid blend at 70°C to obtain a precursor.
[0044] 3. The obtained precursor was evenly spread on the bottom of the crucible, and kept at 750°C for 3 hours under nitrogen protection to obtain a fibrous composite material.
[0045] 4. Put the obtained fiber composite material into a mortar and grind it for 20 minutes to obtain a powdered Fe3C / biomass carbon composite absorbing material.
[0046] The absorbing performance of the Fe3C / biochar composite absorbing material prepared in this embodiment was tested using a vector network analyzer. During the test, the absorbing material powder of the present invention and solid paraffin were uniformly mixed in a mass ratio of 3:7 and made into a ring-shaped sample, and its reflection loss (RL) was tested in the 2-18 GHz electromagnetic wave frequency band. Figure 5 This is the RL curve of the sample in this embodiment at 2~18GHz. It can be seen that the composite material has an RL value of up to -24.9dB at 15.28GHz in the Ku band when the thickness is 5.6mm. When the matching thickness is 8.7mm, the material achieves dual-frequency absorption in the X and Ku bands, and the RL at 9.76GHz in the X band reaches -64.72dB. Embodiment 4:
[0047] The preparation method of the Fe3C / biocarbon composite absorbing material in this embodiment includes the following steps: 1. Prepare 100 mL of NaOH solution A with an alkali concentration of 1%, weigh 4 g of sugarcane fiber and solution A, stir at 100 ° C for 4 hours, and then filter out the sugarcane fiber with a filter; repeatedly wash the sugarcane fiber with deionized water until the pH of the filtered liquid is neutral, and then evaporate the sugarcane fiber in an oven to obtain modified sugarcane fiber.
[0048] 2. Prepare 50 mL of ferric nitrate nonahydrate solution B with a molar concentration of 0.05 mol / L, weigh 1.5 g of modified sugarcane fiber and mix it with solution B, stir at room temperature for 12 hours to obtain a solid-liquid blend; completely dry the solid-liquid blend at 70°C to obtain a precursor.
[0049] 3. The obtained precursor was evenly spread on the bottom of the crucible, and kept at 750°C for 3 h under nitrogen protection to obtain a fibrous Fe3C / biomass carbon composite absorbing material.
[0050] The absorbing performance of the Fe3C / biochar composite absorbing material prepared in this embodiment was tested using a vector network analyzer. During the test, the absorbing material of the present invention was uniformly mixed with solid paraffin at a mass ratio of 3:7 and made into a ring-shaped sample, and its reflection loss (RL) was tested in the 2-18 GHz electromagnetic wave frequency band. Figure 6 This is the RL curve of the sample in this embodiment at 2~18GHz. It can be seen that the composite material obtained an RL value of -11.3dB at 7.0GHz in the C band when the thickness was 3.8mm. When the matching thickness was 7.6mm, the material achieved dual-frequency absorption in the S and X bands, and the RL at 3.1GHz in the S band reached -14.1dB. Compared with Example 2, this embodiment has no other differences except whether the sample is ground or not. Therefore, the results of this example can prove that the performance of the material after grinding is significantly improved.
[0051] The above embodiments are typical embodiments of the present invention and are not intended to limit the present invention in any way. For example, the water bath temperature, water bath time, heat treatment temperature, heat treatment time, material ratio and content, etc. can be further adjusted. Therefore, according to the overall concept of the present invention, the process parameters described by the technicians in the technical field are adjusted and modified, as long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all belong to the protection scope of the present invention.
[0052] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A process for preparing a Fe3C / biomass carbon composite material with S-band wave absorbing performance, characterized in that: Firstly, the sugarcane fiber is modified under high temperature alkaline environment; then the obtained plant fiber and iron salt solution are impregnated at room temperature to obtain a mixture; finally, the Fe3C / biomass carbon composite absorbing material is obtained by sintering in a protective atmosphere to achieve carbonization and in-situ growth.
2. The preparation process according to claim 1, characterized in that The steps include: Step 1: Add sugarcane fiber to NaOH solution, stir and modify it at 100°C for 3-4 hours, filter, repeatedly wash the sugarcane fiber with deionized water until the pH of the filtrate is neutral, and obtain modified sugarcane fiber after drying; Step 2: adding the modified sugarcane fiber obtained in step 1 to a ferric nitrate nonahydrate solution, stirring at room temperature for 12 hours, and then completely drying the solid-liquid mixture at 70° C. to obtain a precursor; Step 3: Sintering the precursor obtained in step 2 in a nitrogen atmosphere to obtain a fibrous Fe3C / biomass carbon composite absorbing material; Step 4: Put the fiber material obtained in step 3 into a mortar and grind it to obtain a powdered Fe3C / biomass carbon composite absorbing material.
3. The preparation process according to claim 2, characterized in that: In step 1, the mass concentration of the NaOH solution is 1%.
4. The preparation process according to claim 2, characterized in that: In step 2, the concentration of the ferric nitrate nonahydrate solution is 0.03-0.07 mol / L.
5. The preparation process according to claim 2, characterized in that: In step 3, the sintering temperature is 750° C. and the holding time is 3 h.
6. The preparation process according to claim 2, characterized in that: In step 4, the grinding time is 20 min.
Citation Information
Patent Citations
An electromagnetic wave absorbing material made from grapefruit peel and its preparation method
CN113023723B
A method for preparing biomass porous carbon microwave absorbing material
CN113122184B
A MOF-derived carbon-based microwave absorbing material with low calcination temperature and its preparation method and application
CN115785905B